2009
DOI: 10.1177/0021998309102398
|View full text |Cite
|
Sign up to set email alerts
|

Limiting Mechanisms of Mode I Interlaminar Toughening of Composites Reinforced with Aligned Carbon Nanotubes

Abstract: Analytical models are presented for the Mode I interlaminar fracture of laminated composites reinforced with aligned carbon nanotubes (CNTs). The models are based on the crack-closure technique for fiber bridging, where the aligned CNTs enhance toughness mechanistically through either pullout (frictional sliding) from the matrix or sword-in-sheath sliding. The models are independent of the scale of reinforcement and demonstrate significant enhanced toughening for nanoscale reinforcement (CNTs) as opposed to ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
93
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 34 publications
4
93
3
Order By: Relevance
“…In past work, vertically aligned carbon nanotubes (VACNTs) placed at the interface (so-termed 'nanostitching' 5 ) of prepreg plies can improve the critical energy release rate 2.5X in Mode I over the baseline composites. This improvement is greater than the results reported for standard z-pinning reinforcement 2,5,13 . Apart from interlaminar toughness, there are other mechanical properties than can benefit from interlaminar reinforcement.…”
Section: Introductioncontrasting
confidence: 59%
“…In past work, vertically aligned carbon nanotubes (VACNTs) placed at the interface (so-termed 'nanostitching' 5 ) of prepreg plies can improve the critical energy release rate 2.5X in Mode I over the baseline composites. This improvement is greater than the results reported for standard z-pinning reinforcement 2,5,13 . Apart from interlaminar toughness, there are other mechanical properties than can benefit from interlaminar reinforcement.…”
Section: Introductioncontrasting
confidence: 59%
“…Further, quantitative modelling of this CNT pull-out mechanism during the fracture of these nanocomposites confirmed that such a mechanism may indeed account for the observed increases in toughness [29,30]. However, pull-out requires the CNTs to debond from the matrix, which may also absorb energy.…”
Section: Introductionmentioning
confidence: 70%
“…Further tests [59] gave a range of values between 15 and 86 MPa. Blanco et al [29] suggested that the value of the interfacial shear strength would lie between 1 and 100 MPa, so 47 MPa is a good estimate for use in this study. Substituting Eq.…”
Section: Fracture Energymentioning
confidence: 87%
See 2 more Smart Citations